(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The concept of the stock market appeared as early as 1791 in Philadelphia. The main stock markets in Europe in the early 19th century were the London and Frankfurt stock exchanges. Such concept, as stock market was developing rapidly, and in 1991, stock market appeared in Uzbekistan. It was in 1991 that the first stage of development of the stock market began and the development continues to this day